The flexible coordination modes of guanidine ligands in Zn alkyl and halide complexes: chances for catalysis - Reinmuth, Matthias; Neuhäuser, Christiane; Walter, Petra; Enders, Markus; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2011)
Due to their high basicity, guanidines are versatile ligand systems. In principal, they could use both their imino and amino nitrogen to establish a dative metal-N bond. However, generally only the imino N of a guanidine ligand is bound to a metal. Herein we present some examples in which both the imino and amino groups of guanidine ligands are directly engaged in the bonding to a metal ion. Under certain conditions the amino group could establish an additional link to a metal center acting as a hemilabile ligand. This result is likely to be of relevance for catalytic reactions, demonstrating the possibility to stabilize a vacancy at the metal (for instance generated by ligand dissociation).
First published: 09 November 2010
Gesehen am 14.09.2022